Iron Age metallurgy at Salūt (Sultanate of Oman): a preliminary note (poster) - Renzi, Martina; Esposti, Michele Degli; Rehren, Thilo (Proceedings of the Seminar for Arabian Studies, 2016)
Extensive excavations at the Iron Age site of Salūt, near Bisyā in central Oman, revealed a complex architecture, allowing the reconstruction of a long history of building activities and rearrangements. Among the discovered structures, none can clearly be associated to metal production, although a small vertical furnace could be tentatively interpreted as a metallurgical structure, possibly used for small-scale copper/bronze remelting. The presence of charcoal-rich deposits, metal scraps, and stored broken objects in its vicinity also points in this direction. A selection of these items, together with some plano-convex ingots from other contexts within the site, has been analysed and the preliminary results are outlined here. The significance of this work is underlined by the current dearth of data on Iron Age metallurgy in the Oman peninsula, compared to comprehensive studies of Bronze Age metal production, when the land of Magan was widely renowned for its wealth of copper ores.